2021
DOI: 10.3390/ijerph18105230
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Patients’ Acceptance in E-Health Clinical Trials

Abstract: Introduction: Telehealth (TH) interventions with Chronic Obstructive Pulmonary Disease (COPD) management were introduced in the literature more than 20 years ago with different labeling, but there was no summary for the overall acceptance and dropout rates as well as associated variables. Objective: This review aims to summarize the acceptance and dropout rates used in TH interventions and identify to what extent clinical settings, sociodemographic factors, and intervention factors might impact the overall acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…We calculated the use rate of telehealth among participants who had experience in telehealth. We defined the use rate as the number of years using telehealth divided by the total amount of clinical experience in years, with the use rate expressed as a proportion [ 15 , 16 , 17 ].…”
Section: Methods and Designmentioning
confidence: 99%
“…We calculated the use rate of telehealth among participants who had experience in telehealth. We defined the use rate as the number of years using telehealth divided by the total amount of clinical experience in years, with the use rate expressed as a proportion [ 15 , 16 , 17 ].…”
Section: Methods and Designmentioning
confidence: 99%
“…The results showed that the acceptance rate was 80%, versus a low dropout rate of 19%. This was the normal response to the uptake of telehealth interventions before the pandemic occurred [ 47 ]. These results indicate that the adoption of telehealth, as well as awareness of the benefits of using telehealth, has reached an advanced level among people with chronic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…All participants reported that they had watched the video link at least once before doing Acapella treatment or ACBT. The success of this approach suggests that for some people the offer of remote support to perform sputum clearance may enhance access 34…”
Section: Discussionmentioning
confidence: 99%